nstitution of Atalykship in the Post-Golden Horde World. - A.V. Belyakov; A.V. Vinogradov; M.V. Moiseev (Золотоордынское обозрение, 2017)
Research objective: To study the institution of atalykship in the Crimean, Siberian and Kazan khanates and the Nogai Horde. Research materials: Published and unpublished sources: books of official orders in the Russian state, chronicles, acts, diplomatic documents, archaeological data, etc. Results and novelty of the research: Up to now the institution of atalykship has not been practically studied. The authors attempted to consider this phenomenon on the example of the Crimean, Siberian and Kazan khanates and the Nogai Horde. Evidence of the presence of atalyks in the service of the Chinggisids in Russia was also taken into account. The authors managed to show that atalyks represented a complex and multifaceted tool in the struggle of the khans with the heads of the els (clans) they controlled. The status of atalyk was based solely on the personal loyalty and affection between the educator and educatee. However, this relationship was beneficial to both sides. A Chinggisid received the faithful conductor of his policy, ready to fulfill his most delicate mission. For his part, the tutor automatically raised his social and material status and helped his relatives’ careers. This, in turn, helped the khan to curb the claims of clan elites. The phenomenon under consideration had many regional features throughout the entire Desht-i Kipchak’s space. We consider the emergence and development of the institution of atalykship on the example of the Crimean khanate. However, this example can not be considered standard. It can not be automatically applied to other territories. Over time, new documents will be found. This will substantially supplement information on this phenomenon in other regions.